2022
DOI: 10.3390/brainsci12010116
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of the COVID-19 Lockdown: A Comparison between Caregivers of Autistic and Non-Autistic Individuals in Italy

Abstract: The COVID-19 outbreak has disrupted the daily routine of the population worldwide, including autistic people and their caregivers, with severe consequences on mental health. On one hand, the reduced social contacts and the interruption of outpatient and daycare services during the lockdown have represented a real challenge for autistic people and their caregivers. On the other hand, confinement has allowed individuals to spend more time pursuing their interests and stay home with their family members without f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
(65 reference statements)
0
5
1
Order By: Relevance
“…Other 5 investigations revealed various results, in contrast to these findings. They suggested that during the lockdown, psychopathological issues in this population 21,28,29,35,38 decreased.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Other 5 investigations revealed various results, in contrast to these findings. They suggested that during the lockdown, psychopathological issues in this population 21,28,29,35,38 decreased.…”
Section: Resultsmentioning
confidence: 98%
“…Evaluation of the Psychological impact of the Coronavirus 141 Fusar-Poli et al/2022 28 This research revealed that the autistic adults' mental health significantly declined.…”
Section: Caregivers Of Autistic Peoplementioning
confidence: 93%
See 1 more Smart Citation
“…However, other research has reported much greater levels of anxiety and depression during the pandemic among carers of children with an intellectual disability when compared to parents of children without intellectual disability ( Willner et al, 2020 ). Another study comparing carers of autistic and non-autistic individuals did not find significant differences in mental health symptoms during the pandemic between these groups ( Fusar-Poli et al, 2022 ). Risk factors for more parental mental health symptoms during the pandemic have included lower pre-pandemic family income and more pandemic-related stressors (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Emerging evidence from around the world has demonstrated that the COVID-19 pandemic and related social and school changes have had a detrimental impact on the mental health and well-being of many autistic people and their families ( Asbury & Toseeb, 2022 ; Crane et al, 2021 ; Manning et al, 2021 ; Toseeb & Asbury, 2022 ; White et al, 2021 ); however, findings across studies are not consistent ( Fusar-Poli et al, 2022 ). For example, caregivers and autistic young people and adults have reported a strong dissatisfaction with the services provided for autistic people during the pandemic, with participants describing a detrimental impact on autistic people’s mental health and well-being ( E. Pellicano et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%